2020
DOI: 10.3389/fneur.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Transthoracic Echocardiography in Diagnostic Evaluation of Ischemic Stroke

Abstract: Objective: Transthoracic echocardiography (TTE) is routinely performed as part of standard acute ischemic stroke (AIS) workup. However, the overall yield of TTE is unclear and many patients may undergo unnecessary investigations. This study aims to investigate the utility of TTE as part of AIS workup.Methods: We collected data on consecutive patients with AIS who were admitted to our institution between 07/01/2016 and 09/30/2017. Patients were included based on neuroimaging-documented AIS, age >18 and neuroima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In patients with infective endocarditis, only 10% of the findings in FDG PET/CT of the heart led to changes in treatment [ 266 ]. Routine transthoracic echocardiography in acute ischemic stroke patients had relevant findings in 38% of patients, however only 8.5% of patients had additional work-up [ 267 ]. Elective coronary angiography investigating coronary heart disease had relevant findings in 40% of patients in one study [ 268 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with infective endocarditis, only 10% of the findings in FDG PET/CT of the heart led to changes in treatment [ 266 ]. Routine transthoracic echocardiography in acute ischemic stroke patients had relevant findings in 38% of patients, however only 8.5% of patients had additional work-up [ 267 ]. Elective coronary angiography investigating coronary heart disease had relevant findings in 40% of patients in one study [ 268 ].…”
Section: Resultsmentioning
confidence: 99%
“…Harris et al 4 found that in patients with known AF, TTE results were less likely to influence treatment changes (adjusted odds ratio, 0.12; 95% CI, 0.006–0.66). Douen et al 24 reported that in 31 patients with newly diagnosed or known AF, TTE identified 1 left ventricular thrombus and moderate to severe left ventricular dysfunction in 2 additional patients with a history of myocardial infarction, suggesting that TTE does not provide relevant results in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a thorough investigation of the patient is important for the proper characterization and management of ischemic stroke. Emerging evidence suggests that atrial enlargement may be a biomarker of AF-independent underlying thrombogenic atrial heart disease with an independent risk of indeterminate or recurrent cardioembolic stroke (17).…”
Section: Discussionmentioning
confidence: 99%
“…The American Heart Association and American Stroke Association (AHA/ASA) guidelines recommend echocardiography for evaluating a patient with ischemic stroke only in selected cases (class IIa/class IIb). A recent study published by Harris et al aimed to investigate the utility of transthoracic echocardiography (TTE) as a part of an acute ischemic stroke workup and revealed that the overall yield of TTE in acute ischemic stroke was low (17). Conversely, TTE has been performed as part of the assessment of stroke patients in recent years.…”
Section: Introductionmentioning
confidence: 99%